Vesicular Antibodies: Shedding Light on Antibody Therapeutics with Cell Membrane Nanotechnology - Zhao, Chenchen; Pan, Yuanwei; Yu, Guocan; Zhao, Xing‐Zhong; Chen, Xiaoyuan; Rao, Lang (Advanced materials (Weinheim), 2023)
The high stability of antibodies and their ability to precisely bind to antigens and endogenous immune receptors, as well as their susceptibility to protein engineering, enable antibody‐based therapeutics to be widely applied in cancer, inflammation, infection, and other disorders. Nevertheless, the application of traditional antibody‐based therapeutics has certain limitations, such as high price, limited permeability, and protein engineering complexity. Recent breakthroughs in cell membrane nanotechnology have deepened the understanding of the critical role of membrane protein receptors in disease treatment, enabling vesicular‐antibody‐based therapeutics. Here, the concept of vesicular antibodies that are obtained by modifying target antibodies onto cell membranes for biomedical applications is proposed. Given that an antibody is basically a protein, as an extension of this concept, vesicles or membrane‐coated nanoparticles that use surface antibodies and protein receptors on cell membranes for biomedical applications as vesicular antibodies are defined. Furthermore, several engineering strategies for vesicular antibodies are summarized and how vesicular antibodies can be used in a variety of situations is highlighted. In addition, current challenges and future prospects of vesicular antibodies are also discussed. It is anticipated this perspective will provide new insights on the development of next‐generation antibodies for enhanced therapeutics. Recent breakthroughs in membrane‐derived vesicle nanotechnology have enabled vesicular‐antibody‐based therapy. By proposing the concept of vesicular antibodies, reviewing their engineering strategies and biomedical applications, and highlighting their unique advantages, this perspective intends to provide new insights on the development of vesicular antibodies.